Cold plasma treatment is safe for diabetic foot ulcers and decreases Staphylococcus aureus bacterial load - Lagrand, Rimke S; Sabelis, Louise We; de Groot, Vincent; Peters, Edgar Jg (Journal of wound care, 2023)
Cold atmospheric plasma (CAP) has antimicrobial properties. We studied the safety of a novel CAP device (PLASOMA prototype; Plasmacure, The Netherlands) that is simple to use and could be applied at a patient's home for the treatment of diabetic foot ulcers (DFUs). Secondary objectives were to investigate the effect of CAP on bacterial load and on ulcer size. We included subjects with non-infected, superficial DFUs and treated them with CAP on a daily basis for 10 days. The primary endpoint was the occurrence of serious adverse device effects (SADE). We defined safety as: ≤10% of patients experiencing a SADE other than infection (non-infectious SADE), and ≤60% of patients developing infection of the foot (infectious serious adverse event (SAE)). We enrolled 20 patients. No SADE occurred, but three infectious SAEs occurred at the site of application within one month of treatment; three SAEs unrelated to treatment occurred, and 55% of subjects reported transient mild adverse device effects. bacterial load decreased directly after CAP application (p=0.01). The mean decrease of ulcer surface area was 43% (95% confidence interval: 20.2%-65.9%). CAP treatment in DFUs was safe and well tolerated. Ulcer size and colonisation decreased during treatment.